Pre-but not post-meiotic senescence affects sperm quality and reproductive success in the North African houbara bustard - Meunier, Léna; Sorci, Gabriele; Abi Hussein, Hiba; Hingrat, Yves; Rehspringer, Noé; Saint-Jalme, Michel; Lesobre, Loïc; Torres Carreira, Janaina (Frontiers in Ecology and Evolution, 2022)
Age-dependent reduction in reproductive success can arise due to deterioration of reproductive physiology. Senescing males have been shown to produce ejaculates with poor sperm quality, which impinges on male reproductive success. In addition to individual age, gamete age can also affect male reproductive success. Accordingly, variance in male reproductive success can be due to pre-meiotic (referring to individual age) and post-meiotic senescence (sperm age). Here, we tested whether male and sperm cell aging have additive or interactive effects on male reproductive success in a bird with a promiscuous mating system, the North African houbara bustard. To assess pre-meiotic aging, we compared male reproductive success between two age classes (3-6- and 12–16-year-old). To infer the effect of post-meiotic aging, male ejaculates were collected at three-time intervals following a common initial collection (day 1, 5 and 10). Therefore, day 1 ejaculates are supposed to contain younger sperm than day 5 and day 10 ejaculates. Following controlled artificial inseminations, reproductive success was assessed using three fitness-linked traits (hatching success, chick growth rate and survival). In addition to reproductive output, we also assessed whether pre- and post-meiotic aging affected a wide range of sperm and ejaculate traits. In agreement with previous reports, we found that males in the older age class produced less sperm with poorer motility compared to young individuals. However, contrary to the prediction, we found that ejaculates collected at day 5 and 10 tended to have better sperm traits such as motility and velocity. The results on sperm traits were generally mirrored in the effect on reproductive success since young males produced offspring that grew faster and had better survival during the first month of life, and eggs fertilized by sperm collected at day 5 had the highest hatching success. In any of the models, there was evidence for interactive effects of male and sperm age. Overall, these results confirm the role of pre-meiotic aging on male reproductive success. The lack of evidence for sperm aging could come from the experimental design but might also reflect the pattern of mating frequency in a species with a lek-based mating system.